Radiological Involvement among Asymptomatic and Symptomatic COVID-19 Patients - A Cross- Sectional Study (Chest & Heart Journal, 2023)
Background and aims: The COVID-19 pandemic is a current problem across the world. Evaluation of the radiological involvement is helpful for early detection of the COVID-19 cases, even when RT-PCR is negative. As RT-PCR is a time-consuming procedure, have high false negative rate, and requires a special laboratory set-up, radiological findings can be used for early detection and proper management of the suspected cases. The aim of this study was to evaluate the radiological involvement (HRCT & chest X-Ray) among asymptomatic and symptomatic COVID-19 patients.Methods: This cross-sectional study was conducted among suspected and confirmed COVID- 19 patients visited at the outpatient department or admitted to the National Institute of the Diseases of the Chest and Hospital (NIDCH), Dhaka, Bangladesh within the period of April 15, 2020 and June 5, 2020. Chest X-Ray and high-resolution computed tomography scan (HRCT) of the chest was done as well as RT-PCR of nasopharyngeal swab for SARS-CoV-2. Sensitivity, Specificity, PPV and accuracy of HRCT and RT-PCR was evaluated.Results: Total 53 cases were enrolled in the study. The mean age was 47.4 years with male predominant (52.8%). RT-PCR was positive in 64.2% cases. Ground glass opacity (GGO) with consolidation was the most common (50.9%) HRCT pattern and the left lower lobe was most commonly involved (60.4%). In chest X-Ray, consolidation was the most common finding (22.6%) followed by GGO (20.8%). HRCT has high sensitivity (73.33%) and specificity (75.0%) in detecting parenchymal abnormality following SARS-CoV-2 infection.Conclusion: Chest X-ray and HRCT can play an important role in the early detection of COVID-19 suspected cases for starting treatment early.Chest Heart J. 2021; 45(2) : 71-77